Motivating and Evaluating Template-Based Content ODP Instantiation: Evaluation Dataset for WOP 2016 Submission - Hammar, Karl (Jönköping University, 2018)
The dataset consists of folders on ODPs, Ontologies, Responses and Surveys.

Content Ontology Design Patterns (CODPs) are typically instantiated into a target ontology or ontology module through a process of specialisation of CODP entities. We find, from experiences in three projects, that this approach leads to ontologies that are unintuitive to some non-expert ontologists. An approach where CODPs are used as templates can be more suitable when constructing ontologies to be used or modified by such users, and we propose a method for such template-based ODP instantiation.

The dataset was originally published in DiVA and moved to SND in 2024.

The dataset consists of folders on ODPs, Ontologies, Responses and Surveys.

Content Ontology Design Patterns (CODPs) are typically instantiated into a target ontology or ontology module through a process of specialisation of CODP entities. We find, from experiences in three projects, that this approach leads to ontologies that are unintuitive to some non-expert ontologists. An approach where CODPs are used as templates can be more suitable when constructing ontologies to be used or modified by such users, and we propose a method for such template-based ODP instantiation.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Motivating and Evaluating Template-Based Content ODP Instantiation: Evaluation Dataset for WOP 2016 Submission
Keywords: data; data; ontologies (information management); ontologier (informationshantering); Computer Sciences; Datavetenskap (datalogi)